Utilizing PRISM and RE-AIM to implement and evaluate the Rural Telementoring Training Center (RTTC) for health care workforce development in rural communities - Melhado, Trisha V.; Schneegans, Suyen; Rochat, Andrea; Kawasaki, Keito; Finley, Erin P.; Wheeler, Denna; Allison, Waridibo E. (Frontiers in Health Services, 2023)
Amid rural health worker shortages and hospital closures, it is imperative to build and maintain the local workforce. Telementoring (TM) or technology-enabled mentoring, is a tool for improving health care quality and access by increasing workforce capacity and support. The national Rural Telementoring Training Center (RTTC) was developed to compile and disseminate TM best practices by delivering free training, tools, and technical assistance to support the implementation, sustainability, and evaluation of new and current TM programs for rural health workers. This paper details how the Practical, Robust Implementation and Sustainability Model (PRISM) was used to understand the context that shaped implementation as well as how Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) was concurrently applied to frame outcomes. The RTTC has three implementation strategies: outreach, training and technical assistance (TTA), and a Quality Measure Toolkit. Ongoing periodic reflections with the RTTC team, informed by PRISM, were collected, as were RE-AIM outcomes. Central to this design was the continuous review of incoming data in team meetings to inform programmatic changes by identifying challenges and applying modifications to strategies in real time. Major implementation changes discussed during reflections included providing timely and relevant messaging through various platforms, streamlining and customizing a TTA approach, and offering different options for accessing the Toolkit. The outreach strategy resulted in high Reach across the US, with over 300 organizations contacted. The effectiveness of the RTTC was demonstrated by counts of people engaging with outreach (ex. over 8,300 impressions on LinkedIn), the website (over 6,400 views), and e-bursts (33% open rate). Moreover, there were 32 TTA requests and 70 people accessing the Toolkit. Adoption was demonstrated by 27 people participating in TTA and 14 individuals utilizing the Toolkit. The integration of PRISM and RE-AIM frameworks promoted a holistic implementation and evaluation plan. Using PRISM, the RTTC team was able to reflect on the implementation strategies through the lens of contextual factors and make rapid programmatic changes within team meetings. That process resulted in outcomes framed by RE-AIM. The integration of two frameworks in tandem provided an adaptive and comprehensive approach to implementing a large-scale, national program.